RANCANG BANGUN MESIN PENCETAK PAKAN TERNAK UNGGAS DENGAN SISTEM PENGGERAK MOTOR LISTRIK - Muh. Nurul Haq Amaluddin; Windi Mudriadi; Sabdha Purna Yudha (Journal of Energy, Materials, & Manufacturing Technology, 2023)
Along with the development of technology in the field of animal husbandry, it is necessary to have a simple tool that can help and relieve farmers in feeding livestock, especially for poultry. Therefore, a poultry feed molding machine is needed which is expected to help relieve farmers both in providing feed, saving time and costs for workers. The working principle of this poultry feed molding machine sequentially is that when the electric motor drive is turned on, a mixture of animal feed ingredients is inserted into the funnel, Engine power will be channeled to the axle screw conveyor through a V-belt transmission by tightening the pully tensioner which functions to stir animal feed ingredients. Animal feed ingredients that have been mixed evenly will be herded out to the end of the tube by the axle screw conveyor. The animal feed mixture will come out through the printer and will be cut by the blade, so that poultry feed is formed in the form of pellets. The test results of the poultry feed printing machine with a tool power speed of 653 rpm can produce 126 kg / hour of animal feed.